(untitled) (Cadernos de Sociomuseologia, 2019)
This thesis discusses the specificities of Museum Education as the learning that results from collective process of the museum making appropriation; this is, in the scope of participatory museologies or Sociomuseology. It aims to produce an understanding of musealization that favors Brazilian communities, which develop processes of cultural preservation, to recognize themselves in the field of Social Museology and, simultaneously, to provide the academic and public policies fields with epistemological, theoretical and methodological bases to legitimate these initiatives on an equal footing with professional and institutional heritagerelated practices. Therefore, it builds an intercultural view of Sociomuseology, anchored in the memory of de[s]colonized museologies and ‘heartened’ from Biology of Knowledge, Good Living and Ubuntu. This is a critical-collaborative action research, committed to cognitive justice and social transformation in the sense of decoloniality. It starts from the experience lived in Image Pedagogy Program, implanted in the Campinas Museum of Image and Sound – SP, in the period between 2003 and 2018, to build situated knowledge about Museum Education. The Analectic Method structures the cartography of Campinas cultural territories, embracing its multiple dimensions: the dystopia of the hegemonic matrix, the utopia of border education actions and the heterotopia of transformative inventions. Keywords: Analectic Method; Decoloniality; Interculturality; Museum Education; Sociomuseology.